Asset Securitization and Optimal Retention - Kiff, John.; Kisser, Michael (Washington, D.C. : International Monetary Fund, 2010)
This paper builds on recent research by Fender and Mitchell (2009) who show that if financial institutions securitize loans, retaining an interest in the equity tranche does not always induce the securitizer to diligently screen borrowers ex ante. We first determine the conditions under which this scenario becomes binding and further illustrate the implications for capital requirements. We then propose an extension to the existing model and also solve for optimal retention size. This also allows us to capture feedback effects from capital requirements into the maximization problem. Preliminary results show that equity tranche retention continues to best incentivize loan screening.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet